2012
DOI: 10.21273/hortsci.47.5.589
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework to Consider Endogenous Hormonal Control of Apple Tree Flowering

Abstract: Inhibition of flower initiation by nearby developing fruits is one of the main causes of biennial bearing in apple trees. This localized inhibition may depend on a critical ratio of inhibitor and promoter hormones that inhibits flowering of apical meristems. A model is proposed to explain this phenomenon. In the model, it is assumed that seeds and leaves act as point sources and export inhibiting and promoting hormones to apical meristems. The model assumes critical ratios of promoting and inhibiting h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Thus, contrary to previous reports showing that application of GA 3 , GA 4 , or GA 7 during flowering could affect the following year's bloom (Westwood, 1993;Tromp and Wertheim, 2005;Pellerin et al, 2012), no such phenomenon was observed in the present research (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, contrary to previous reports showing that application of GA 3 , GA 4 , or GA 7 during flowering could affect the following year's bloom (Westwood, 1993;Tromp and Wertheim, 2005;Pellerin et al, 2012), no such phenomenon was observed in the present research (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Crop load management is particularly important for 'Honeycrisp' because it can limit inconsistent annual flowering and fruit set (Embree et al, 2007), improve fruit quality (Baugher and Schupp, 2010), and decrease susceptibility to storage disorders (Robinson and Watkins, 2009). 'Honeycrisp' has exhibited an extreme predisposition to overcropping, therefore, is susceptible to biennial bearing (Crassweller et al, 2005;Embree and Nichols, 2005;Robinson and Watkins, 2003;Wright et al, 2006), especially when thinning is completed too late (Pellerin et al, 2011(Pellerin et al, , 2012. Thinning is a common agronomical practice to optimize crop load to improve fruit size and quality as well as reducing biennial bearing (Dennis, 2000;Link, 2000;Wertheim, 2000).…”
mentioning
confidence: 99%
“…Theories to explain the effect of fruiting on flower formation generally fall into three categories: 1) plant growth regulators (Guitton et al, 2012;Krasniqi et al, 2013;Pellerin et al, 2012), 2) source-sink competition (Bruchou and G enard, 1999;Palmer et al, 1991;Saa and Brown, 2014), and 3) the interaction between plant growth regulators and sink-source competition (Smith and Samach, 2013;Untiedt and Blanke, 2001).…”
Section: Discussionmentioning
confidence: 99%